2001
DOI: 10.1210/jc.86.8.3787
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Insomnia Is Associated with Nyctohemeral Activation of the Hypothalamic-Pituitary-Adrenal Axis: Clinical Implications

Abstract: Although insomnia is, by far, the most commonly encountered sleep disorder in medical practice, our knowledge in regard to its neurobiology and medical significance is limited. Activation of the hypothalamic-pituitary-adrenal axis leads to arousal and sleeplessness in animals and humans; however, there is a paucity of data regarding the activity of the hypothalamic-pituitary-adrenal axis in insomniacs. We hypothesized that chronic insomnia is associated with increased plasma levels of ACTH and cortisol. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
364
1
26

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(419 citation statements)
references
References 0 publications
28
364
1
26
Order By: Relevance
“…First, some studies 35,36) found that job stress is related with the increase of cortisol, and it was reported that cortisol and the activity of hypothalamic-pituitary-adrenal (HPA) axis are associated with sleep disorder 37,38) . Accordingly, the activation of HPA axis by job stress is likely to cause sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
“…First, some studies 35,36) found that job stress is related with the increase of cortisol, and it was reported that cortisol and the activity of hypothalamic-pituitary-adrenal (HPA) axis are associated with sleep disorder 37,38) . Accordingly, the activation of HPA axis by job stress is likely to cause sleep disorder.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1967, Monroe 104 showed that poor sleepers had increased body temperature, vasoconstrictions, body movements, and skin resistance as compared with good sleepers. Insomnia has also been associated, in some studies, with increased 24-h metabolic rate (as measured by oxygen consumption), 27 , 105 24-h adrenocorticotropic hormone and cortisol levels, 51 and heart rate. 106 Some investigators have demonstrated greater inhibition of facial muscle activity and increased cardiac vagal tone in response to sleep-related emotional stimuli among individuals with insomnia as compared with good sleepers.…”
Section: Physiologic Hyperarousalmentioning
confidence: 99%
“…However, there is an increasing body of literature regarding the psychological and physiological differences between insomniacs and good sleepers. Several studies have demonstrated a greater prevalence of intrusive thoughts, worry, and rumination [8], poor sleep hygiene [9,10], dysregulation of the hypothalamic pituitary axis [11], elevations in sympathetic activity [12], and metabolic rate [13], increased daytime alertness [14], and elevated high-frequency electroencephalographic (EEG) activity [15][16][17] in patients with insomnia compared to good sleepers.…”
Section: Introductionmentioning
confidence: 99%